The Effectiveness of Muscle Energy Technique in Reducing Pain and Disability With Patients Lateral Epicondylitis - Ayu Sri Wahyuni Novianti, I Gusti; Ayu Astiti Suadnyana, Ida; Dhita Prianthara, I Made (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background: Lateral epycondylitis is a disorder experienced by individuals who often use their hands during activities such as tennis athletes or people who like to play tennis, housewives and office workers. Repeated hand movements will cause inflammation in the muscles and tendons on the lateral side of the elbow, causing pain and interfering with activities. This problem can be overcome with exercises in the form of muscle energy technique. This exercise uses isometric muscle contractions that lead to muscle relaxation reflexes that reduce tissue tension and improve joints. Objective : This study aims to determine the effectiveness of muscle energy technique in reducing pain and disability in patients with lateral epicondylitis Research Methods/ Implementation Methods : TThis study is a pre-experimental study with a pre-test and post test one group design conducted at one of the clinics in Denpasar for 4 weeks. The sample of this study was 14 people in accordance with the inclusion and exclusion criteria. The sampling technique is purposive sampling. The research instruments used the Visual Analog Scale to measure pain and the Patient-Rated Tennis Elbow Evaluation to measure disability. Results : The reduction in pain and disability before and after the intervention using the paired sample t-test was obtained p<0.001 respectively Conclusion/Lesson Learned : Based on the results of the study, it can be concluded that the muscle energy technique is effective in reducing pain and disability in patients with lateral epicondylitis.